Keefektifan Waktu Aerasi Menggunakan Bubble Aerator Dalam Menurunkan Kadar Besi (Fe) Air Sumur Desa Kebarongan Kemranjen Banyumas Tahun 2016 - Mubarak, Alfian; , Heru Subaris Kasjono, SKM,. M.Kes; , Dwi Astuti, SKM, M.Kes (2016)
Water for daily needs to be qualified chemical parameters, levels of iron in the water. Iron levels wells villagers kebarongan who researched, all above the threshold value, With the highest levels of iron 2,02 mg / l. One method water treatment to lower levels of iron is with aeration use bubble aerator. The purpose of this research to know effectiveness of time using bubble aerator in lowering water levels of iron. The kind of research this is true experiment with pretest-posttest with control group. The population research Is a whole well water kebarongan village. The sample collection technique is purposive of sampling with sample is well water is about iron highest. Statistical analysis use the anova one line with the results of value p value ≤ 0,0001, the further use post hoch test lsd to know the time most effective to lower levels of iron with the result mean difference largest 1,41000 In treatment with long aeration 40 minutes, where time 40 minutes is the most effective to lower the levels iron with effectiveness of 73,15% can be lowered levels of the iron becomes 0,53 mg / l. Advised, That the iron water meet the quality of drinking water so the process aeration using bubble aerator coupled with the process of filtration.